Ade, Wida dan Dhiva EKSTRAKURIKULER PENDIDIKAN AGAMA ISLAM : STRATEGI MENINGKATKAN MINAT BELAJAR SISWA TERHADAP AGAMA - Ade Ayu Angeliah; Dhiva Munaya Al Hasy; Nurwida Elvina Harun (Cendekia Madani Nusantara, 2024)
ABSTRACT This research aims to explore effective strategies in increasing students' interest in learning about Islamic Religious Education through extracurricular activities. The research uses qualitative methods with a liberal research approach. This research was carried out by identifying the topic to be researched, searching for information through various sources, selecting and evaluating information, and carrying out information analysis to identify themes and patterns from the information used. From the results of the analysis, it can be concluded that there are several effective strategies in increasing students' interest in learning about Islam through extracurricular Islamic religious education. These strategies are the use of interesting media, the use of creative learning methods, and the development of varied extracurricular programs. Keywords: Extracurricular; Strategy; interest in learning; Pai